The impact of brand image on purchase decision - Febby Adhani Martadina; Hairul Anwar (KINERJA, 2023)
The Impact of Brand Image on Purchase Decision of TRESemme in Samarinda, under Hairul Anwar, SE., MA as the advisor. The purpose of this research is to determine the effect of Corporate Image, User Image and Product Image on Purchase Decision. The type of data used in this research is quantitative data by using primary data and questionnaire is the research instrument. In this research the population is all consumers who have used TRESemmÃ© products, especially the shampoos and conditioners in addition have been using the product for about a month. The sampling technique used is non-probability technique with purposive sampling method and data sampling was obtained 112 respondents. The data was collected by using online questionnaire given directly to the respondents via Google Form. Data analysis using multiple linear regression with the help of SPSS (Statistical Package for Social Sciences) version 25. The result obtained shows that (1) Corporate Image has an insignificant negative effect on Purchase Decision. (2) User Image has a significant positive effect on Purchase Decision. (3) Product Image has a significant positive effect on Purchase Decision.